2022
DOI: 10.1080/07853890.2022.2075914
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of maintenance dialysis patients with COVID-19: mortality and risk factors from a developing country

Abstract: Patients on maintenance dialysis therapy are especially vulnerable to COVID-19 and its complications. This study aimed to assess the incidence, epidemiological characteristics, and mortality rate of COVID-19 among maintenance dialysis patients. This retrospective observational chart review study included 548 patients from all dialysis units in the West Bank of Palestine who acquired COVID-19 between 5 March 2020, and 11 August 2021. We collected data on patients' demographics, clinical features, and outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Both the aging of the population and the outbreak of COVID-19 have led to increased rates of ESRD and the number of elderly patients needing PD (10). In order to improve the prognosis and quality of life in elderly patients with PD, we need to understand the factors influencing their survival and actively prevent and control these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Both the aging of the population and the outbreak of COVID-19 have led to increased rates of ESRD and the number of elderly patients needing PD (10). In order to improve the prognosis and quality of life in elderly patients with PD, we need to understand the factors influencing their survival and actively prevent and control these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous variables are expressed as mean ± standard deviation (SD) or median and interquartile range (IQR), as appropriate. Group differences were tested with the χ 2 test or Fisher test. The independent samples t -test or Mann-Whitney-U test was used for continuous variables, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…In hemodialysis patients, a SARS-CoV-2 infection is associated with a markedly increased morbidity and mortality in comparison to the general population with a mortality rate of more than 20% in hospitalized patients [1][2][3] . In the last two years we have learned that double vaccination might not be enough to achieve adequate long-term immune protection in all hemodialysis patients and triple vaccination offers significantly better protection against COVID-19 in this patient group 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple comorbidities and limited treatment options for COVID-19 infection [5] caused the extremely high infection rate and mortality of MHD patients [3,6,7] . In this regard, if the MHD patients with COVID-19 who are likely to develop pneumonia can be identi ed at an early stage, it can help strengthen surveillance and intervention early to reduce the mortality of MHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Older age was one of the independent risk factors for death in COVID-19 patients, which was the common result of most studies, as well as the results of studies in MHD patients, older than 50 ~ 65 years old were the high-risk age for death in MHD patients [4,9,10] . Some studies reported that males might be one of the risk factors [7] , but most studies did not reach relevant conclusions. We found that age over 65 years was a risk factor pneumonia in COVID-19 patients, and gender has no signi cant relationship with pneumonia, which was similar to the results of most studies analyzing risk factors for death.…”
mentioning
confidence: 99%